Analysis of the Balmer series in several exoplanet atmospheres - Fardella, Valerio (My University, 2023)
The study of exoplanet atmospheres is a relatively new research field that requires sophisticated and highly precise instruments. In this thesis, I analyzed the Balmer lines as well as the sodium, Na I, and calcium, Ca II, doublets in the atmospheres of four gas giants and one neptunian planet: KELT-20 b, KELT-6 b, WASP-69 b, WASP-107 b, and GJ-3470 b. These planets present different temperatures and other physical properties among them. The data used for analysis were collected by HARPS-N, a high-resolution spectrograph (R = 115,000) mounted on the Telescopio Nazionale Galileo. These data were obtained during multiple primary transits of the planets. During a primary transit, a fraction of the star’s radiation passes through the planet’s atmosphere and is partially absorbed, producing a spectrum depending on the planet atmosphere. To extract this spectrum, several procedures were employed, including removal of telluric lines and correction of the stellar contamination. To validate the methodology used in this thesis for analyzing the atmospheric spectra, I examined the Hα line of KELT-20 b, which has been previously studied by Fossati et al. (submitted). The authors reported a value of the line’s depth of (0.78 ± 0.03)%, while the value I obtained was (0.79 ± 0.03)%. This consistency confirms the reliability of the method and its applicability to other targets and lines of interest. Although the Hα and Hβ lines could not be detected in some planets, possibly due to low signal-to-noise ratio or stellar activity, I estimated the upper limit to the depths for some of them. Additionally, for most targets, I performed an average between the planet’s Hα and Hβ lines to search for evidence of hydrogen presence in the atmosphere. Finally, I compared the heights of the atmospheres obtained from the line depths with their respective Roche lobe radii to investigate possible evaporation effects caused by the gravitational influence of the host star.
Keywords: planets and satellites: atmospheres, techniques: spectroscopic